2008
DOI: 10.2165/00003088-200847090-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of the Phosphate Binder Lanthanum Carbonate

Abstract: Lanthanum carbonate is considered to be the most potent of a new generation of noncalcium phosphate binders used to treat hyperphosphataemia in chronic kidney disease (CKD), a condition associated with progressive bone and cardiovascular pathology and a markedly elevated risk of death. Its phosphate-binding action involves ionic binding and precipitation of insoluble complexes within the lumen of the intestine, thereby preventing absorption of dietary phosphate. While pharmacokinetics have little relevance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 54 publications
7
57
0
1
Order By: Relevance
“…In the past, carbonate, calcium acetate, and sevelamer were often used for this purpose, but with unsatisfactory results. LC, a novel aluminum-free, calcium-free phosphate binder with low oral bioavailability of lanthanum [24] dissociates in the upper gastrointestinal tract after oral administration and binds phosphate released from food [25]. Several studies have demonstrated the therapeutic effect of LC on hyperphosphatemia [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, carbonate, calcium acetate, and sevelamer were often used for this purpose, but with unsatisfactory results. LC, a novel aluminum-free, calcium-free phosphate binder with low oral bioavailability of lanthanum [24] dissociates in the upper gastrointestinal tract after oral administration and binds phosphate released from food [25]. Several studies have demonstrated the therapeutic effect of LC on hyperphosphatemia [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adverse events graded severe or serious showed no relevant differences between treatment groups, and none of these events were considered by the investigators treating the affected patients to be related to study treatment. The most frequent causes of discontinuation due to adverse events were hypophosphatemia (PA21, n=13 [10 . No other adverse events led to study discontinuation in more than one participant except for diarrhea in two sevelamer-HCl participants.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…The kidney is not significantly involved in the clearance of lanthanum, the main excretion route for absorbed lanthanum being via the liver into bile (Damment and Pennick 2007). Consistent with this hepatobiliary excretion, the plasma exposure and pharmacokinetics of lanthanum are similar in healthy individuals and patients undergoing dialysis (Damment and Pennick 2008). Recently, the utilizations of lanthanide metal salts and organolanthanoid compounds as a reagent or catalyst in organic synthesis have steadily increased Yanada et al 2001).…”
Section: Please Scroll Down For Articlementioning
confidence: 94%